Morbidade e mortalidade de pacientes com choque séptico tratados comnoradrenalina: estudo multicêntrico - Arnaldo Santos Leite (2009)
Among patients admitted into intensive care units (ICU), 9% present septic shock. More than 50% of them die. The implementation of rapid treatment is essential, with immediate usage of antibiotics, infectious focus elimination, if applicable, and supportive treatment. First, the supportive treatment is based in fluid resuscitation and the use of vasopressors. Other measures such as artificial ventilation, nutrition, inotropic support, glucose control, corrections of electrolytic and acid-basic imbalance are also essential for the patients recovery.Norepinephrine has been the vasopressor of choice, used frequently above usual doses. The aim of this study was to evaluate the morbidity and mortality of patients with septic shock who used norepinephrine. The importance of other intervening variables in the outcome of septic shock patients was also analyzed. We enclosed 289 septic shock patients admitted in the ICUs of seven hospitals of Minas Gerais between May 1st, 2004 and December 31st, 2005 who used norepinephrine. The patients were followed everyday until the patients discharge. It was possible to identify the site of infection in 93.4% (270/289) of studied patients: lung (54.3%), abdomen (24.6%), urinary tract (6.6%), skin and soft tissue (3.1%) and others (4.8%). In 6.6% of patients it was not possible toidentify the site of infection. The median of the index of APACHE II was 16.Among the 289 patients, the ICU mortality was 68.9%. All the 65 patients who used norepinephrine above 2.37 mg/kg/min died before being discharged from ICU. When the patients were compared, the group which used higher doses of norepinephrine used pulmonary artery catheter and intra-arterial catheter more often, received more frequently artificial ventilation, dobutamine and midazolam, had a higher APACHE II index, used higher dose and more time of dobutamine, with lower time of use of central venous pressure monitoring and artificial ventilation. When the different cut-off points of maximum dose of norepinephrine are compared, a statistical difference in ICU mortality was also observed. Themaximum dose of norepinephrine among patients who survived in the ICU was 2.37 mg/kg/min. Among the nonsurvivors, norepinephrine was used until the dose of 14.5 mg/kg/min. Also, the nonsurvivors had a higher APACHE II index, were submitted to hemodialysis, intra-arterial catheter monitoring and artificial ventilation more often, received a higher dose of dobutamine and developed more often acute renal failure. This study showed that age, sex, hospital, site of infection, use of corticoids, dopamine, dobutamine, fentanyl, midazolam, number of co-morbidities, dose of dopamine, duration of norepinephrine use and implement of haemodynamic monitoring were not associated with ICU mortality inseptic shock patients. The APACHE II index, the dose of norepinephrine and the development of an acute renal failure were independently associated to a higher ICU mortality rate. In this sample, the norepinephrine dose was a marker for ICU mortality. Norepinephrine dose above 0,785 mg/kg/min pointed to bad outcome and above 2.37 mg/kg/min did not show benefit because the ICU mortality in this last group was 100%.